Соответствие методики государственных испытаний трехкомпонентных нейтрализаторов выхлопных газов реальным условиям эксплуатации - Nicolay Gavrilovich Pevnev; Alexei Vasil'evich Zaloznov (Вестник СибАДИ, 2017)
In this article reviewed design features and conditions for effective operation of the three-way catalytic converters of exhaust gases, installed on automobile with gasoline internal combustion engines. Shown work opportunities of the converters in cold start and warm-up conditions of the engine. Revealed the optimal work mode of the converter, whereby it effectively comply its functions. Analyzed and described the methodology of state testing converters of exhaust gases. In the article descibed winter conditions operation of automobiles with spark ignition engines and three-way catalytic converters of the exhaust gases. Analyzed the real work conditions of the automobiles with converters, revealed negative points of winter operation of the vehicles with converters. Shown the discrepancy of the technical regulations to the real conditions of operation of the automobiles with converters with regard to the region with a cold climate and to the Omsk city in particular.